Sintering densification behavior of ZnO–SnO2 binary ceramic targets. Issue 1 (8th September 2022) - Huai, Zhiyuan; Chen, Jie; Qi, Chao; Sun, Benshuang; Liu, Shuhan; Song, Hongming; He, Jilin
Abstract: In this work, high‐performance ZnO–SnO2 binary ceramic targets for magnetron sputtering of transparent conductive oxide (TCO) films were prepared by pressureless oxygen atmosphere sintering. The sintering behavior and densification mechanism of the ZnO–SnO2 binary targets were analyzed by systematically studying the oxide powder state, formation process of the solid reaction phase, and evolution of the target microstructure. The data revealed that the ZnO–SnO2 powder treatment improved the sintering activity and the powder dispersion; furthermore, it promoted a mutual reaction between the different components during sintering and the homogeneity of the target composition. The densification of the pure SnO2 ceramic target was difficult to achieve, and the addition of ZnO led to a continuous interaction between the ZnO and SnO2 components. The Zn2 SnO4 phase started to form, and a temporary shrinkage of the target occurred above 800°C. After formation of the stable Zn2 SnO4 and SnO2 phases, the target shrunk rapidly with increasing temperature, densification occurred during growth, and the two phases started to interact. The sintering temperature provided the driving force for the target densification, with the densification activation energy of the ZnO–SnO2 binary ceramic target estimated to be 580 kJ/mol based on the master sintering curve. A binary ceramic target with a high density (99.78% relative density), a fine grain size, and a homogeneous phase structure was achieved at a temperature of 1600°C. These findings are promising for the further improvement and performance enhancement of SnO2 ‐based materials.